2010
DOI: 10.1186/1471-2164-11-400
|View full text |Cite
|
Sign up to set email alerts
|

De novo characterization of a whitefly transcriptome and analysis of its gene expression during development

Abstract: BackgroundWhitefly (Bemisia tabaci) causes extensive crop damage throughout the world by feeding directly on plants and by vectoring hundreds of species of begomoviruses. Yet little is understood about its genes involved in development, insecticide resistance, host range plasticity and virus transmission.ResultsTo facilitate research on whitefly, we present a method for de novo assembly of whitefly transcriptome using short read sequencing technology (Illumina). In a single run, we produced more than 43 millio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
291
6
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 352 publications
(342 citation statements)
references
References 31 publications
(38 reference statements)
44
291
6
1
Order By: Relevance
“…Of all the unigenes, 33 276 (45.0%) had BLAST hits in the Swiss-Prot database. Compared with Wang et al (2010b), in which only 16.2% had BLAST hits in Nr database, the higher percentage in the present study was partially ascribed to the higher frequency of long sequences (Wang et al, 2010b). As reported by Parchman et al (2010), longer contigs were more likely to have BLAST matches in the protein database.…”
Section: Functional Annotation By Searching Against Public Databasessupporting
confidence: 48%
See 1 more Smart Citation
“…Of all the unigenes, 33 276 (45.0%) had BLAST hits in the Swiss-Prot database. Compared with Wang et al (2010b), in which only 16.2% had BLAST hits in Nr database, the higher percentage in the present study was partially ascribed to the higher frequency of long sequences (Wang et al, 2010b). As reported by Parchman et al (2010), longer contigs were more likely to have BLAST matches in the protein database.…”
Section: Functional Annotation By Searching Against Public Databasessupporting
confidence: 48%
“…A primary platform being used to generate transcriptomic resources is the Illumina short read sequencing platform, followed by de-novo assembly of sequence reads. This approach has been used to characterize transcriptomes of diverse taxa, including plants (Chang et al, 2011;Garg et al, 2011), insects (Wang et al, 2010b;Xue et al, 2010), mollusks (Feldmeyer et al, 2011), fish (Xiang et al, 2010), and mammals (Yao et al, 2012a;2012b). Despite their obvious benefits, NGS methods have not yet been applied to turtle research.…”
Section: Introductionmentioning
confidence: 99%
“…Chilling injury occurs in loquat fruit when they are stored at temperatures lower than 5°C, and fruit stored at 0°C exhibits severe symptoms of lignification and tissue browning, and a decrease in the percentage of juice (Cai et al, 2006c). Wang et al (2010) identified five components of the ethylene signal transduction pathway from ripening loquat fruit and found that the EjETR1 and EjEIL1 genes may be involved in chilling injury development. However, the expression profiles of these genes under low temperature stress are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome analyses are a cost-effective method for the characterization of species that lack a fully sequenced genome [7,8]. The short reads from Illumina paired-end sequencing can provide a deep sequencing coverage for the accurate base calling in de-novo transcriptome assembly and has been utilized to characterize many non-model species [37][38][39][40]. However, no transcriptome sequencing data is available for menhaden.…”
Section: Discussionmentioning
confidence: 99%